Natural variation in gene expression and viral susceptibility revealed by neural progenitor cell villages - Wells, Michael F.; Nemesh, James; Ghosh, Sulagna; Mitchell, Jana M.; Salick, Max R.; Mello, Curtis J.; Meyer, Daniel; Pietilainen, Olli; Piccioni, Federica; Guss, Ellen J.; Raghunathan, Kavya; Tegtmeyer, Matthew; et al. (Cell stem cell, 2023)
Human genome variation contributes to diversity in neurodevelopmental outcomes and vulnerabilities; recognizing the underlying molecular and cellular mechanisms will require scalable approaches. Here, we describe a “cell village” experimental platform we used to analyze genetic, molecular, and phenotypic heterogeneity across neural progenitor cells from 44 human donors cultured in a shared in vitro environment using algorithms (Dropulation and Census-seq) to assign cells and phenotypes to individual donors. Through rapid induction of human stem cell-derived neural progenitor cells, measurements of natural genetic variation, and CRISPR-Cas9 genetic perturbations, we identified a common variant that regulates antiviral IFITM3 expression and explains most inter-individual variation in susceptibility to the Zika virus. We also detected expression QTLs corresponding to GWAS loci for brain traits and discovered novel disease-relevant regulators of progenitor proliferation and differentiation such as CACHD1. This approach provides scalable ways to elucidate the effects of genes and genetic variation on cellular phenotypes. [Display omitted] •Brief overexpression of NGN2 converts human stem cells to functional NPCs•Molecular and cellular phenotypes are measured in hPSC-derived NPC “villages”•An IFITM3 SNP explains most inter-donor variation in NPC viral susceptibility•CACHD1 is a novel regulator of neurogenesis Wells et al. describe an experimental platform that pools rapidly generated neural progenitor cells from multiple human donors into the same culture flask to detect the genetic factors associated with molecular phenotypes and to identify an IFITM3 single nucleotide polymorphism that explains a sizable proportion of inter-donor variation in Zika virus vulnerability.